KAJIAN VARIABILITAS CURAH HUJAN DI KAWASAN LERENG GUNUNG MERAPI DENGAN UJI MANN-KENDALL - Endita Prima Ari Pratiwi; Joko Sujono; Rachmad Jayadi (Universitas Lambung Mangkurat, 2012)
Rainfall is one of hydrology components that may be affected by climate change. The change of rainfall pattern can cause much impact on many fields. Many researches about global and regional climate change projection have been conducted. However, research about local scale of climate change based on climate character in local area is still necessary for a better result. Area of this research cover southwest slope of Merapi Mount, Java Island, Indonesia. Automatic rainfall data records from 1989 until 2008 of nine rainfall gauges in Merapi Mount’s southwest slope is available. Those data series this research is only adequate for climate variability analysis. The methods to detect trends in this research is non parametric test (Mann-Kendall test). The results show that at level of significance 5%, trend of rainfall in Mt. Merapi slope area is statistically not performing a specific pattern. Wet season occur every November until April while dry season occur every May until October. Neglect of trend signification, annual rainfall has decreace tendency. Rainfall amount in the beginning of wet season has increase tendency while rainfall amount in the middle of wet season and dry season have decreace tendency. Maximum daily and hourly rainfall also have decreace tendency.Spatially, annual rainfall and maximum daily rainfall increased from lower to higher elevation, from east to west and from south to north.